Work-Family factors and its relationships between dispositional, occupational characteristics and intention to stay - Noraani Mustapha; Jegak Uli; Aminah Ahmad; Khairuddin Idris (2011)
This study was conducted to test the mediating effects of work-family factors on the relationships between dispositional and occupational characteristics as the independent variables and intention to stay as the dependent variable. By using self-administered research questionnaire, data was collected from 240 middle age single mother employees in Klang Valley, Malaysia. Samples were determined through simple random sampling method whereby six out of 24 single mother associations were selected to obtain research samples. Descriptive statistical analysis was conducted to describe the respondents. Pearson Product Moment Correlation was used to determine the relationships among variables and Structural Equation Modeling using AMOS version 16.0 was utilized for model testing and to verify the presence of mediation effects. Further, the Soble’s z-test was used to test whether the mediators carry the effect of the independent variables on the dependent variable. The findings indicated that there were positive relationships among variables. The results also established the presence of mediation effects between the independent and dependent variables. Organizations may utilize work-family factors as mechanism to promote longer retention among employees.